Wide-Bandwidth and High-Sensitivity Measurement Technique of Intrinsic Modulation Response of Semiconductor Lasers - Nobuhide Yokota; Tomoharu Nohara; Hiroshi Yasaka (IEEE Photonics Journal, 2023)
We propose and demonstrate a measurement technique of the intrinsic modulation responses of semiconductor lasers with high sensitivity in a wide modulation frequency range. The technique is based on the two-tone optical modulation and lock-in detection of an optical spectrum having modulation sidebands. The measured modulation response of a conventional 1.55-μm distributed feedback laser indicates that the lock-in detection improves the signal-to-noise ratio by 22 dB. This significant improvement allows measurement of the modulation response up to 75 GHz even though the 3-dB bandwidth of the distributed feedback laser is only 11 GHz. Our technique is suitable for evaluation of the intrinsic modulation response of wide-bandwidth semiconductor lasers free from device parasitic effects.